A possible link between famine exposure in early life and future risk of gastrointestinal cancers: Implications from age‐period‐cohort analysis. Issue 3 (7th November 2016) - Xie, Shao‐Hua; Lagergren, Jesper
Abstract : The Chinese famine in 1958–1962 was one of the worst in human history, but its potential influence on cancer risks is uncertain. Using cancer incidence data in Shanghai, China, during 1983–2007, we calculated age‐specific incidence rates of gastrointestinal cancers in birth cohorts exposed to the Chinese famine in different periods of life and a non‐exposed reference cohort. Age‐period‐cohort regressions estimated the overall relative risks of gastrointestinal cancers in each birth cohort. A total of 212, 098 new cases of gastrointestinal cancer were identified during the study period (129, 233 males and 82, 865 females), among whom 18, 146 had esophageal cancer, 71, 011 gastric cancer, 55, 864 colorectal cancer, 42, 751 liver cancer, 9, 382 gallbladder cancer and 14, 944 had pancreatic cancer. The risk of esophageal, gastric, colorectal and liver cancers was higher in cohorts exposed to the Chinese famine in early life than in the reference cohort, except for esophageal cancer in women. The risk of esophageal, liver and colorectal cancers was particularly high in men exposed to famine during early childhood (0–9 years). There were no clear associations between famine exposure and the risk of pancreatic or gallbladder cancer. This study suggests an increased risk of esophageal, gastric, liver and colorectal cancers associated with childhood exposure to the Chinese famine. These findings indicate a need for further investigations confirming the results and identifying the underlying mechanisms. Abstract : What's new? Famine may increase risk of certain cancers, according to new analysis. Malnutrition at a young age can lead to health issues including hypertension, diabetes and respiratory issues, but has not yet been linked to cancer. These authors examined cancer risks in the wake of the Chinese famine of 1958–1962, one of the worst ever recorded. Using cancer incidence data, they compared risk among cohorts of people who weathered the famine at different stages of life. Compared with people born after the famine's end, those exposed at a young age had increased rates of esophageal, gastric, liver and colorectal cancers.